Incentive mechanism for customer collaboration in product development: An exploratory study - Chunguang Gu; Yang Yang (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The purpose of this paper provides some appropriate incentive factors for customers who collaboration in product development, and analyzes the mechanism and degree of these incentive factors influence on customer's positivity and working efforts. Design/methodology/approach: This paper first proposes the economic incentives and non-economic incentives according to the characteristics of customer collaborative product development. Then the firm and customer's objective function and constraints are determined based on their income and costs that produce in the process of customer collaborative product development. On this basis, this study then analyzes the relationship between the incentive factors and customer's positivity and working efforts. Findings: The results show that: the fixed salary shows no motivational effect but basic guarantee. The performance salary has more influence on promoting customers' efforts than the efforts of helping other customers. The team share incentive affects both effort levels equally. The better spiritual incentive, the higher firm's effort level, the better innovative environment, and the more motivate customer collaboration in product development. Practical implications: The results of this paper can help firms to understand the influence of different incentive factors, and offer them with references to determine incentive factors and its degree. Originality/value: This paper provides a comprehensive incentive mode, which including economic incentive factors and non-economic incentive factors. Moreover, the paper provides an insight on the relationship between these incentive factors and customer's positivity and working efforts.
Keywords: 650; product development; customer collaboration; economic incentive; non-economic incentive